(untitled) (Signifiances (Signifying), 2023)
In this article we are interested in the uses of quizá as an introducer of an indirect interrogative clause (Quizá cuánto tiempo ‘who knows how long’), constructions considered inadmissible in all Spanish speaking areas except Chile, where these uses are on the contrary massively attested since the 20th century without supplanting the traditional uses of the form as an epistemic adverb (’maybe’). From the theoretical framework of signifier linguistics and its recent extensions (submorphemic analysis), we will show that the Chilean diatopism, far from threatening the monosemy of this adverb, is neither the trace of a historical remotivation nor of a new stage of grammaticalisation, but an extreme and especially meta-linguistic interpretation of a unique and invariant signified which shapes the identity of this adverb in the Pan-Hispanic system.